Central mechanisms of pain in orofacial pain patients: Implications for management. (2nd July 2020) - Jessri, Maryam; Sultan, Ahmed S.; Tavares, Tiffany; Schug, Stephan; Farah, Camile S.; Balasubramaniam, Ramesh
Abstract: Background: Central sensitization (CS) is a form of neuroplasticity characterized by changes in the neural sensitivity, responsiveness, and/or output that are not contingent on peripheral input nor activity‐dependent. CS is characterized by activation of unmyelinated C‐fibers resulting in a cascade of events at molecular and cellular levels which eventuate into generation of synaptic currents at rest. CS, therefore, contributes to heightened generalized pain sensitivity, further complicates the process of reaching a diagnosis, and increases the possibility of treatment failure. Body: Trigeminal nerve is the main sensory supplier of the anterior part of the head, including the intraoral structures. Primary afferent nociceptors of the trigeminal nerve and low threshold mechanoreceptors synapse with wide dynamic range (WDR) neurons in the pons. This multifaceted network of nerve interactions which is further complicated by the modulatory circuits that can suppress or heighten the activity of WDR neurons is one of the main contributors to CS. The importance of CS in orofacial pain disorders is emphasized in the context of chronic pain development. As for all chronic pain conditions, it is crucial to consider the biopsychosocial aspects of chronic orofacial pain in managing this diverse group of conditions. This review highlights current understanding of the biopsychosocial model and central mechanisms contributing to the pathogenesis of chronic orofacial pain.